2006
DOI: 10.1002/polb.20794
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of branching in disordered materials

Abstract: ABSTRACT:The phenomenon of structural branching is ubiquitous in a wide array of materials: polymers, ceramic aggregates, polymeric networks, and gels. Branching has a strong influence on the structureproperty relationships of these materials. Despite the interdisciplinary importance and decades of effort, the analytical description and quantification of branching are weak. Existing techniques for polymers based on size exclusion chromatography and rheology are, at best, qualitative, and quantitative character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…Polymer branch content can be determined using various techniques such as GPC, NMR, rheology, and small-angle scattering [25]. Based on the structures of the starting reagents, it is anticipated that the macromers will contain short-chain branches as opposed to long-chain branches (molecular weight indistinguishable from the main chain).…”
Section: Synthesis Of Macromersmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer branch content can be determined using various techniques such as GPC, NMR, rheology, and small-angle scattering [25]. Based on the structures of the starting reagents, it is anticipated that the macromers will contain short-chain branches as opposed to long-chain branches (molecular weight indistinguishable from the main chain).…”
Section: Synthesis Of Macromersmentioning
confidence: 99%
“…Based on the structures of the starting reagents, it is anticipated that the macromers will contain short-chain branches as opposed to long-chain branches (molecular weight indistinguishable from the main chain). GPC, small-angle scattering, and rheology are techniques that are useful for determining long-chain branching as opposed to short-chain branching [25] and could not be used for macromer characterization in this work. Although high-frequency (188.6 MHz) 13 C NMR can be used to quantify shortchain branching, it is limited to high levels of short-chain branching because it is very difficult to assign chemical shift values to side chains greater than six or more carbon atoms in length [25].…”
Section: Synthesis Of Macromersmentioning
confidence: 99%
“…The mechanism of reinforcing is largely associated with the chemical and physical interactions between the polymer matrix and the filler . Kulkarni et al and Niedermeier et al reported that there are several known mechanisms of filler reinforcement: sorption and chemisorption of the polymer molecules on the filler's surface, occlusion of the polymer macromolecules between the filler's voids, formation of an adhesive layer in the interphase boundary, chemical reactions between the chemical groups of the polymer and the filler, and dissipation of the critical stress in polymer macromolecules by the sliding on the filler's surface. The reinforcing effect of a filler depends on its characteristics, such as size and shape of the particles, specific surface area, surface activity, hydrodynamic effect, tendency to create a structure in the elastomer matrix, and the strength of the polymer‐filler interactions .…”
Section: Introductionmentioning
confidence: 99%
“…[12] Small angle scattering (SAS) of X-rays and neutrons can yield structural information from branched or aggregated systems over multiple size-scales. [13a,13b] In recent works by Beaucage, [14] and Kulkarni and Beaucage, [15] it has been proposed that SAS data could potentially yield topological information from such systems. In this communication, we make an attempt to apply this approach to small angle neutron scattering (SANS) data from the existing literature.…”
Section: Introductionmentioning
confidence: 99%